Effect of retention time on biohydrogen production by microbial consortia immbolised in polydimethylsiloxane - Ismail, Isnazunita; Hassan, Mohd Ali; Abdul Rahman, Nor'aini; Chen, Sau Soon (Academic Journals, 2011)
An investigation on biohydrogen production from palm oil mill effluent (POME) was conducted in a continuous stirred tank reactor seeded with polydimethyl-siloxane (PDMS) immobilised mixed cultures at adjusted retention time. The hydrogen-producing bacteria obtained from an anaerobic digester used for treating POME were acclimatised and immobilised in PDMS. The immobilised cultures were assessed for their effectiveness in generating hydrogen in a continuous system. In this study, the PDMS cultures were fed with raw POME at hydraulic retention times of 6, 4 and 2 days and operated at controlled pH and temperature of 5.5 and 55°C, respectively. At hydraulic retention time (HRT) 2 days, the average hydrogen production rate per unit volume of POME was 2.1 NL/L/d. Hydrogen constituted up to 43% of the total gas produced and methane was not detected throughout the 150 days of continuous operation. The soluble carbohydrate degradation efficiency was highest at 81.2% during HRT 4 days and the concentration of soluble metabolites produced, followed the order of acetic > butyric > ethanol > propionic acid. The microbial diversity of the immobilised consortia determined by denaturing gradient gel electrophoresis (DGGE) changed at different HRTs; with increasing dominant species phylogenetically related to Clostridaceae.